MedMetrics: biometrics passports in medical and clinical healthcare that enable AI and blockchain - Lu, HY (IntechOpen, 2022)
The term biometrics was defined to suggest any measurable biological and biomedical metrics that can be used to identify and confirm the uniqueness of individuals. In this chapter, we would like to introduce an emerging area of biometrics, MedMetrics, that combines patient and drug information managed in coded passports to keep medical information accessible, safe and fraud-resistance. Medmetics includes medical and biological biometrics of patients based on their electronic health records, International Classification of Disease codes, Anatomical Therapeutic Chemical codes, Defined Daily Doses, time-series test results, and personalizsed biological data. By combining the blockchain technology, Medimetrics enables sensitive data sharing in between different clinical settings, allowing monitoring patients’ health and care, as well as avoiding identification-related medical mistakes or frauds. MedMetrics Blockchain Passport can be used to identify patients and confirm their previous health conditions without the right of modifying or removing previous records. Medmetrics can revolutionary change the user demographic, shift safety restrictions, define new user applications, and encourage ethical AI regulations in medical science and health care. This chapter will discuss these directions and provide insights into the next generation of biometrics in medical science and health care.